A Simplified Successive Ionic Layer Adsorption and Reaction (s-SILAR) Method for Growth of Porous BiVO4 Thin Films for Photoelectrochemical Water Oxidation. Issue 2 (18th January 2017) - Guo, Wenlong; Tang, Ding; Mabayoje, Oluwaniyi; Wygant, Bryan R.; Xiao, Peng; Zhang, Yunhuai; Mullins, C. Buddie
Abstract : Since monoclinic bismuth vanadate (BiVO4 ) has been considered to be a promising anode material for photoelectrochemical (PEC) water splitting, the synthesis of high-quality BiVO4 photoanodes for use in PEC cells is beneficial. Here, we report a facile simplified successive ionic layer adsorption and reaction (s-SILAR) method to synthesize porous BiVO4 films. Evaluation of the porous BiVO4 film as a photoanode yielded photocurrents of ∼0.70 and ∼1.20 mA cm −2 at 1.23 V vs RHE under AM1.5G irradiation for water and sulfite oxidation, respectively. After coupling with a cobalt–phosphate (Co-Pi ) catalyst, its photocurrent for water oxidation increased to ∼0.97 mA cm −2 at 1.23 V vs RHE. The high performance of the resultant BiVO4 films and simplicity of operation make this s-SILAR technique a promising strategy to prepare BiVO4 photoanodes.